Deteksi Bola Menggunakan Kombinasi Metode Filter Warna dan Bentuk Untuk Pengindraan Robot Soccer - suheryadi suheryadi (Jurnal Poli-Teknologi, 2020)
Robot soccer is a combination of sports, robotics technology, and multi agent system, to achieve goals. Besides requiring individual intelligence, it also requires the ability to work together between individuals. The main problem in robot soccer is detecting objects in the form of balls. These problems include varying lighting that produces shadows from the ball, there are objects similar to balls, as well as real-time detection. Ease and lightweight program implementation are also needed in detecting the ball so that it is easy to implement on embedded systems. Computer vision technology helps robot soccer in detecting balls.Therefore, an alternative process is proposed to detect the ball using a combination of color filters and the shape or contour of the object. The results obtained from the experiments showed relatively effective in object detection, with a recall value of 90,69%.